ON THE IMPLEMENTATION OF ECOLOGICAL AND HYGIENIC RESEARCH IN THE INDUSTRIAL REGION - Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Корсакова, Татьяна Георгиевна; Мотуз, Ирэна Юрьевна; Штайгер, Варвара Адамовна (Medicine in Kuzbass, 2021)
Subject of research – atmospheric emissions and working conditions of employees of industrial enterprises of the Kemerovo region. Objective of research – assessment of the impact of environmental and industrial factors on health for risk management and the development of preventive measures. Methods of research. When assessing the risk to public health from exposure to atmospheric emissions from industrial enterprises, the volumes of maximum permissible emissions were used. For calculations based on the map, the points of exposure to concentrations in different areas of the city were selected. The maximum and average annual concentrations were calculated using the Ecocenter-Standard program. The assessment of the risk to public health from exposure to atmospheric emissions of the enterprise was carried out on the basis of the Manual 2.1.10.1920-04. The obtained risk values were compared to the acceptable levels. The hygienic characteristics of the factors during the labor process of employees of industrial enterprises were carried out using data from sanitary laboratories and the results of their own measurements which were evaluated by using the Manual 2.2.2006-05. Occupational risk from the impact of production factors and safe work experience were calculated according to the method of A. P. Mikhailuts. Main results. Environmental risks were assessed and the impact of adverse environmental factors on public health was studied. There were identified the main pollutants. The risks of chronic intoxication and carcinogenic risks were calculated considering the points of exposure to the concentrations. The total risks of chronic intoxication and carcinogenic risk were compared to acceptable levels in the selected microdistricts of the city. The hygienic working conditions of the employees of the main industries, as well as the regularities of the influence of the factors of the production environment on their health, were studied. Conclusion. The unfavorable environmental state and the production environment in the industrial region is the main factor for the deterioration of the health in the population, which requires constant study to develop a system of measures to preserve health.